2000
DOI: 10.1348/000712600161961
|View full text |Cite
|
Sign up to set email alerts
|

Running shared mental models as a distributed cognitive process

Abstract: Shared mental models theory normally takes the individual as its unit of analysis. This paper proposes a theoretical framework for studying shared mental models in which the model is considered to be distributed amongst the team. From this framework a cognitive process is predicted which describes how shared mental models are run. A team reasoning task requiring planning was used to illustrate this framework and test predictions derived from it. Two aspects of sharing mental models were studied; the degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 20 publications
1
65
0
1
Order By: Relevance
“…Tschan et al 2000) but also in generic laboratory settings (e.g. Banks and Millward 2000). The findings from these studies generally suggest that a strongly shared mental model is advantageous for team performance.…”
Section: Cognitive Diversity In Teamsmentioning
confidence: 69%
“…Tschan et al 2000) but also in generic laboratory settings (e.g. Banks and Millward 2000). The findings from these studies generally suggest that a strongly shared mental model is advantageous for team performance.…”
Section: Cognitive Diversity In Teamsmentioning
confidence: 69%
“…The wellbeing of team members is dependent upon on the shared understanding and trust that safety is 'assured and not assumed'(K. Miller, Riley, & Davis, 2009). The concept of shared mental models (SMM) was first described fifteen years ago in demanding and critical environments such as military training (Banks & Millward, 2000) and flight simulation (Mathieu, Heffner, Goodwin, Salas, & Cannon-Bowers, 2000) to maximises both team process and performance (Mathieu et al, 2000). Studies suggest that shared mental models facilitate teamwork skills (Westli et al, 2010) teamwork performance (Gillespie et al, 2010) and team member anticipation of other staff needs (B.…”
Section: Nursing Teamworkmentioning
confidence: 99%
“…Cannon-Bowers and Salas (2001) make four structural distinctions: overlapping (e.g., common understanding of disease to facilitate reliable diagnosis), similar or identical (i.e., attitudes and beliefs that help team members "make sense" of a situation in a similar way), compatible or complementary (e.g., different specialist knowledge contributing to a common goal) and distributed (i.e., knowledge required to complete a complex task is apportioned among inter-dependent members to reduce the work load). Banks and Millward (2000) found that it was distributed compatible rather than shared knowledge which accounted for performance improvements in their simulated navigation task.…”
Section: Proposition 5 Cognitive States -Shared Cognitionmentioning
confidence: 97%